Varieties of employment: a comparison of skill-based activities at work among youth and young adults in Canada. Issue 5 (1st November 2020) - Pullman, Ashley; Chen, Michelle Y.
ABSTRACT: According to practice engagement theory within the field of adult education, everyday workplace activities offer an opportunity for skill development among youth and young adults; yet, prior research highlights the prevalence of routine and low-skill work within entry-level jobs. Utilising data from the Programme for the International Assessment of Adult Competencies (PIAAC), the objective of the following study is to demonstrate how workplace literacy, numeracy, and problem-solving activities differ among people aged 16 to 34 in Canada. Latent class analysis provides a typology of literacy, numeracy, and problem-solving activities at work and generates insight into how socio-demographic and employment factors are associated with each group. The findings highlight that employment cannot be uniformly characterised as low-skill. Rather, there are unique employment groups with differing literacy, numeracy, and problem-solving activity characteristics. Nevertheless, socio-demographic factors do matter for gaining access to employment that involves daily skill-based activities. While age, parental education, immigration background, and education level are significantly associated with the latent classes, economic and employment characteristics reduce the magnitude of these associations. Together, the results suggest that access to skill-based activities at work are more or less accessible for certain groups and connect to other aspects of early-career job quality and occupational segregation.